Mobile Application For Language Learning Systems - Hadi Suprayitno; Anugerah Heny (IT for Society, 2020)
Language has a fundamentally social function.Processes of human interaction along with domain-generalcognitive processes shape the structure and knowledge oflanguage. Recent research in the cognitive sciences hasdemonstrated that patterns of use strongly affect how languageis acquired, is used, and changes. This research is to develop anapplication for learning French, Korean, Japanese Palembangand Basa Jawa Languanges. Syntax, semantics and sentencestructure for each language must be considered in the design.Android is chosen to make this application able to be used inmobile fashion. Gathering and Analyzing Data related to eachlanguage is conducted first before carrying out design andcoding the system. Conclusion is withdrawn from the systemtesting and its evaluation results.